Quality appraisal of clinical guidelines for the management of constipation according to AGREE II instrument (Research, Society and Development, 2022)
Constipation is one of the most frequent complaints in health establishments, affecting approximately 20% of the world population. The key to the successful management of this disorder is its early identification and immediate treatment with nondrug measures as the main therapeutic alternative. While clinical guidelines are informative documents that include recommendations aimed at optimizing patient care, this study aims to evaluate the quality of these documents available in the management of this condition. This study evaluated clinical guidelines available in databases, scientific societies and class councils, which had as their theme the management of constipation. The methodology used to evaluate the quality of these documents was the application of the AGREE II instrument. Kappa test of agreement between evaluators was applied to corroborate uniformity in application of the AGREE II instrument. Of the eleven documents analyzed, only three presented the criteria for recommendation proposed for use in clinical practice, with a general average of quality indexes ranging from 93 to 72%. One guideline was recommended with modifications in its structure, with a general average of quality indexes of 44%. The mean overall score among the analyzed documents was 49.01%. Methodological care and expression of information in a concise and clear way, both of the content and methodology employed, result in documents of great quality, however, no aspects were present in most of the guidelines analyzed. Furthermore, it is observed that there are still points that should be improved.